Studying the Effect of Potato Cold Hardening on Integrity of Meristems, Cryopreserved by Slow Freezing - Stribul, T. F.; Shevchenko, N. A.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2006)
Cold hardening effect on potato meristem integrity at two-step cryopreservation has been studied. Such cryoprotectants as dimethyl sulfoxide (DMSO) and 1,2-propanediol (1,2-PD) have been used. Freezing of hardened potato apexes under DMSO protection was established to increase their integrity in comparison with the same index in non-hardened meristems. Potato apex hardening is inexpedient when using 1,2-PD. Observation for cryopreserved meristem development within 30 days has demonstrated that treatment with cryoprotectants and freezing inhibit an apex growth in comparison with the control. 1,2-PD occurred to be less toxic. DMSO treatment can cause callus-genesis.